The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18662/lumproc.rsacvp2017.78
|View full text |Cite
|
Sign up to set email alerts
|

The Self Efficacy of the Emerging Adult, Student or Graduate

Abstract: This research aimed to highlight a model of self-efficacy in emerging adults (ages 18/20 -30 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The period between 20 and 26 years seems to be the most appropriate for the implementation of support programs to prevent the consequences of poor perception of self-efficacy. Self-efficacy is also related to self-personal coherence (Stomff and Vasiliu, 2017). According to the Big Five model, decreasing early maladaptive schemas can improve personality factors (e.g., Sava, 2009;Thimm, 2010;Lungu and Stomff, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The period between 20 and 26 years seems to be the most appropriate for the implementation of support programs to prevent the consequences of poor perception of self-efficacy. Self-efficacy is also related to self-personal coherence (Stomff and Vasiliu, 2017). According to the Big Five model, decreasing early maladaptive schemas can improve personality factors (e.g., Sava, 2009;Thimm, 2010;Lungu and Stomff, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We have proceeded to grouping the participants, based on age, based on the constatation regarding self-efficacy model (Stomff & Vasiliu, 2017). Previous research has shown that self-efficacy is the best predictor of academic performance (Karademas & Kalantzy, 2004;Van Der Westhuizen, De Beer, & Bekwa, 2011;Di Benedetto & Bembenutty, 2013;Di Giunta et al, 2013;Sadri, 2011;Bin Hasan, Bin Hossain, & Islam, 2014;Lane, Lane, & Kyprianou, 2004;Afari, Ward, & Khine, 2012).…”
Section: Resultsmentioning
confidence: 99%